Calculation, simulation and fast estimation of thermal resistance of rotary voice coil actuators. Issue 6 (16th March 2022) - Hu, Jianhui; Wu, Jiaxin; Chen, Jinhao; Li, Yong; Ren, Liuyang; Wang, Qian; Liu, Chengjun
Abstract: Rotary voice coil actuator (RVCA) is mainly used for reciprocating drive of small inertia loads in a limited range of angle, which is widely used in aerospace and other fields. Thermal resistance is one of the most important parameters of RVCAs, which is directly related to the steady‐state temperature rising and operation reliability. Because the thermal resistance cannot be measured directly, the analytical method is usually used to calculate the thermal resistance of the RVCA. However, due to the particularity of the thermal circuit calculation, the calculation is complicated and the result is not accurate. It is not conducive for engineering applications of this kind of actuator. In this paper, a series of rotary voice coil motor is selected as the research object. Through analytical calculation and thermal simulation, a more accurate thermal resistance calculation correction model and thermal resistance value of RVCAs are obtained, and the accuracy of the estimation results is verified by experiments. On this basis, the effective volume of the coil frame of the RVCA is selected as the variable, and the concise variation law of the series thermal resistance data is obtained. This paper provides a fast and accurate estimation method for the thermal resistance of RVCA, which has an important reference value for expanding the engineering applications of RVCAs.